The Relationships Between Egg Production, Age and The Hatching Traits of Pheasants - Ahmet Uçar; Musa Sarıca (Turkish Journal of Agriculture: Food Science and Technology, 2018)
Pheasant rearing is rated in three main categories: show and hobby, public interest, and stocking for game birds and edible purposes. The goal of this pheasant breeding station is to put stocking for game birds in their natural habitat, mainly in the Karadeniz region. Contribution to the issues related to incubation in this station and determination of effective reproduction age by setting production period. The aim of this study is to determine how significant performance criteria like egg production, fertility, hatchability and embryonic mortality are, depending on age and on seasonal changes. Our research has been carried out at the Gelemen Pheasant Breeding Station in Samsun. The pheasant breeds that are used on the farm are made up of 114 male and 800 female pheasants (1♂:7♀), of Hungarian and Caucasian genotypes. During the egg-laying period, which lasts for 16 weeks from the end of March (at the age of 45 weeks) to the middle of July (at the age of 60 weeks), egg production was recorded daily and evaluated once a week, and incubation yield was recorded nine times in total. Differences between weeks of age, in terms of egg production, egg and chick weights, fertility rate, incubation yield and embryonic mortality, have been found to be statistically significant. However, hatchability has been found to be statistically insignificant.